2020
DOI: 10.1177/1077559520941919
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment, Early Adult Substance Use, and Mediation by Adolescent Behavior Problems

Abstract: The purpose of the current study was to examine the potential mediating effects of internalizing and externalizing problems at ages 14, 16 and 18 between types of childhood maltreatment and alcohol and marijuana use problems and disorders in young adulthood. Data were from 473 young adults who participated in the Longitudinal Studies of Child Abuse and Neglect (LONGSCAN). Path analysis was conducted to examine pathways between maltreatment type (birth through age 12), internalizing and externalizing problems a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 68 publications
2
25
0
Order By: Relevance
“…Although the reliability of this source is high, detection of exposed individuals may be lower due to unreported cases to authorities. As some researchers ( 40 ) have previously observed, “rates of retrospective self-report of child maltreatment are generally much higher than rates of agency confirmation, which raises the possibility of maltreated youth being misclassified.” Previous research has indicated that substantiated childhood maltreatment is no better at predicting outcomes than alleged ( 46 ). A recent review has identified that individuals who report abuse prospectively and retrospectively may represent different populations ( 47 ); consequently, it is important to compare differences between cross-sectional and prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reliability of this source is high, detection of exposed individuals may be lower due to unreported cases to authorities. As some researchers ( 40 ) have previously observed, “rates of retrospective self-report of child maltreatment are generally much higher than rates of agency confirmation, which raises the possibility of maltreated youth being misclassified.” Previous research has indicated that substantiated childhood maltreatment is no better at predicting outcomes than alleged ( 46 ). A recent review has identified that individuals who report abuse prospectively and retrospectively may represent different populations ( 47 ); consequently, it is important to compare differences between cross-sectional and prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our path model results revealed that lower self-esteem was associated with greater internalizing and externalizing behavior problems, and that parameter estimates were higher for internalizing behavior problems (standardized parameter estimates: −0.45 to −0.12) than for externalizing behavior problems (standardized parameter estimates: −0.13 to −0.10). Given that internalizing behavior problems are difficult to detect and may have long-term consequences, such as psychopathology and substance use disorders in adulthood (Dubowitz et al, 2020;Gawęda et al, 2020), our findings highlight the need to address adolescent mental health.…”
Section: Notementioning
confidence: 91%
“…external world, such as aggression and delinquency (Achenbach & Rescorla, 2001). Internalizing and externalizing behavior problems during adolescence (a critical time to establishing lifetime behavior) may endure and escalate in adulthood to influence individual health (Dubowitz et al, 2020;Schuler et al, 2015). Not all adolescents who experience childhood victimization exhibit the same behavior problems, likely due to individual differences in how childhood victimization affects development, including development of self-esteem (Brumley et al, 2017;Ju & Lee, 2018).…”
mentioning
confidence: 99%
“…Furthermore, Latinx adolescents reported higher rates of substance use compared to non-Latinx THE MEDIATING ROLE OF SELF-REGULATION adolescents, with 34% reporting past-month alcohol consumption (Kann et al, 2018). However, these studies did not evaluate the potential impact of child maltreatment, a known risk factor for substance use initiation and lifetime use (Dubowitz et al, 2021;Proctor et al, 2017). In studies that do examine this association, the focus is limited to predominantly non-Latinx samples.…”
Section: Maltreatment and Substance Use Among Latinx Youthmentioning
confidence: 99%
“…These findings support the non-equivalence assumption, which asserts that different types of maltreatment (e.g., sexual abuse, physical abuse, emotional abuse, neglect) lead to disparate outcomes (Vachon et al, 2015). For example, studies point to physical abuse as a more robust predictor of adolescent substance use, as compared to other types of abuse (Bayly et al, 2022;Dubowitz et al, 2021;Moran et al, 2004;Norman et al, 2012;Tonmyr et al, 2010). In addition, studies have found that emotional abuse and neglect are more highly associated with substance use compared to other types of maltreatment (e.g., (Afifi et al, 2012;Kisely et al, 2020;Wilson & Widom, 2010).…”
Section: Substance Use and Maltreatment Typementioning
confidence: 99%